Doctrinal Foundations of the Ash’arite Creed - Ben Bouchaib, Fatima (International Journal of Education, Culture, and Society, 2026)
This study examines one of the foundational pillars of Islam—faith and creed (ʿaqīdah and īmān)—with particular emphasis on the theological contributions of the Ashʿarī school. It explores the core principles, key issues, and interpretative frameworks developed by Ashʿarī theologians, aiming to render the Ashʿarite creed more accessible to contemporary audiences while elucidating its foundations, objectives, and role as a representative Sunni doctrine marked by moderation and balance. Central to the study is the question of the primary theological underpinnings of Ashʿarism and how these differ from other doctrinal traditions. Through a dual methodology—descriptive, in presenting the views of prominent Ashʿarī scholars, and comparative-analytical, in examining their arguments and theological constructs—the research offers a structured analysis of Ashʿarī positions within the broader landscape of Islamic theology. The findings affirm that Ashʿarism constitutes a distinct Sunni theological paradigm grounded in rational moderation, rejecting both extremism and rigid literalism. Its synthesis of revealed texts with rational deliberation serves as a safeguard against intellectual and doctrinal deviation, thereby reinforcing its enduring relevance in guiding Islamic thought and preserving theological integrity.